Sovereignty between Effectiveness and Legitimacy: Dimensions and Actual Relevance of Sovereignty in Bodin, Hobbes and Rousseau - Asbach, Olaf (Eurostudia, 2006)
According to a widespread understanding, the idea and the reality of state-sovereignty are in crisis, and may even have come to an end. The state is becoming a “cooperative” state which is no longer capable of imposing its will, and is thus but one social actor among others. This diagnosis relies on a concept of sovereignty which is basically defined by the capacity of the state to organize and rule society. The present article inquires into the conceptual basis of this kind of description, analysis and critique. Are we dealing with an appropriate analysis of current developments? Are the dimensions of state sovereignty, associated in historical and systematic perspective, adequately described? In order to answer these questions the article goes back to the foundations of modern sovereignty, its practical dimensions and its concomitant problems as outlined in Bodin, Hobbes and Rousseau.